Sensory acceptability of iron-fortified red lentil (Lens culinaris Medik.) Dal - Podder, Rajib; Khan, Shaan M.; Tar’an, Bunyamin; Tyler, Robert T.; Henry, Carol J.; Jalal, Chowdhury; Shand, Phyllis J.; Vandenberg, Albert (Institute of Food Technologists (IFT), 2022)
This article was published in the Journal of Food Science [© 2018 Institute of Food Technologists® ] and the definite version is available at : https://doi.org/10.1111/1750-3841.14066 The Journal's website is at: https://ift.onlinelibrary.wiley.com/doi/full/10.1111/1750-3841.14066